2008
DOI: 10.1073/pnas.0708308105
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and redox potential of AhpC, a bacterial peroxiredoxin

Abstract: Typical 2-Cys peroxiredoxins (Prxs) are ubiquitous peroxidases that are involved in peroxide scavenging and/or the regulation of peroxide signaling in eukaryotes. Despite their prevalence, very few Prxs have been reliably characterized in terms of their substrate specificity profile and redox potential even though these values are important for gaining insight into physiological function. Here, we present such studies focusing on Salmonella typhimurium alkyl hydroperoxide reductase C component (StAhpC), an enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
149
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 61 publications
11
149
0
4
Order By: Relevance
“…For other Cys-based peroxidases, substrate specificity correlates well with hyperoxidation rates (8,(37)(38)(39), which is consistent with the fact that oxidation to Cys-SOH and hyperoxidation are both reactions dependent on hydroperoxide concentration (Fig. 3A).…”
Section: Resultssupporting
confidence: 65%
“…For other Cys-based peroxidases, substrate specificity correlates well with hyperoxidation rates (8,(37)(38)(39), which is consistent with the fact that oxidation to Cys-SOH and hyperoxidation are both reactions dependent on hydroperoxide concentration (Fig. 3A).…”
Section: Resultssupporting
confidence: 65%
“…3B) is consistent with this hypothesis. The high catalytic efficiency of the 2-Cys Prxs with k cat /K m values of ∼10 7 M −1 ·s −1 and high affinity with K m values in the μM range (20)(21)(22) presumably ensure rapid oxidation kinetics of their Trx partner in response to small changes in low peroxide levels (24,25). In turn, the identified preference of ACHT4 disulfide transfer reaction toward APS1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Study of the thylakoids-associated ACHT1 revealed that it transmits a disulfide-based oxidative signal in feedback regulation of photosynthesis under homeostasis growth conditions (6). ACHT1 oxidation is driven by 2-Cys Prx, a peroxidase with a low K m for hydrogen peroxide (20)(21)(22) that is conceivably required for the low level of ROS that are typical in signaling events. ACHT1 undergoes rapid redox state changes during the transition of plants from dark to light and afterward, such that, after a short period of net reduction, the ACHT1 pool is maintained in a partially oxidized state in the light.…”
Section: Significancementioning
confidence: 99%
“…Bi-substrate Kinetic Analysis of Prx1 and Prx2-To determine the kinetic parameters, Prxs, AhpFNTD, and TrxA were pre-reduced by 100 M excess of DTT and then DTT was removed as described by Parsonage et al (15,21). Various concentrations of H 2 O 2 were added to the mixtures of pre-reduced Prx1 (100 nM) and AhpFNTD (5-30 M) in the reaction buffer (50 mM Hepes-NaOH, pH 7.0), and then incubated at 25°C.…”
Section: Nad(p)h Consumption Assay-peroxidase Activity Of Prx2 Was Dementioning
confidence: 99%